The Relevance of Explanatory First-Person Approaches (EFPA) for Understanding Psychopathological Phenomena. The Role of Phenomenology - Schmidt, Philipp (Frontiers in Psychology, 2018)
The main aim of this paper is to demonstrate the contributions of Phenomenology-inspired approaches to the explanation of psychopathological phenomena. Section 1 introduces the notion of Explanatory First-Person Approaches (EFPA) which share the assumption that the explanation of consciousness and conscious phenomena necessitates, at least partially, phenomenal facts which function as explanans. With phenomenal facts it is referred to facts about structures and processes of consciousness. To differentiate phenomenology from other EFPA and to extract its distinctive feature, it is compared to the method falling under the category of EFPA which it overlaps with the most: new introspective methods as recently described. Section 2 presents genetic phenomenology as the distinctive feature of phenomenology and shows how particularly genetic phenomenology complements biological explanations of psychopathological phenomena in the context of psychiatric disorders such as schizophrenia. Section 3 presents Cognitive Theory as the most acknowledged EFPA in the broader scientific community, demonstrates its limitations in explaining conscious phenomena in the context of psychological disturbances such as depression, and shows how genetic phenomenology can complement the cognitive approach in a significant way. The overall argument for the significance of phenomenology is as follows: Genetic phenomenology renders phenomenology a distinctive kind of EFPA; genetic phenomenology can complement one of the most dominant non-EFPA accounts in the science of psychiatric disorders: biological reductionism; genetic phenomenology can complement the most dominant existing EFPA in the science of psychological disturbances: Cognitive Theory.